2020
DOI: 10.1016/j.curtheres.2020.100613
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practice and Associated Factors Among Health Care Providers Working in Public Hospitals in Northwest Ethiopia During 2017

Abstract: Background: Despite the fact that evidence-based practice (EBP) is believed to be associated with improved health, safety, and cost outcomes, most medical practice in low- and middle-income countries such as Ethiopia is not evidence-based. Understanding the extent of and barriers to EBP in Ethiopia is important for learning how to best to improve quality of care. Few studies have assessed EBP in Ethiopia. Objective: This study aimed to assess reported level of EBP and associated factors among health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 34 publications
2
28
0
3
Order By: Relevance
“…For example, a recent study in Ethiopia showed that half of health care providers were unable to find resources for implementing an evidence-based practice that attributed to lack of training and poor health facility infrastructures, such as computers and internet. 50 Therefore, there is a pressing need to develop an evidence base that addresses the requirements of the developing countries and getting this evidence into the hands of those who deliver healthcare is fundamental to improvements in healthcare delivery and health outcomes. 51 The findings from this study can provide useful up-to-date evidence on the landscape of SR and MA research and it is a wake-up call to balance generation of new knowledge and implementation by decision-makers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study in Ethiopia showed that half of health care providers were unable to find resources for implementing an evidence-based practice that attributed to lack of training and poor health facility infrastructures, such as computers and internet. 50 Therefore, there is a pressing need to develop an evidence base that addresses the requirements of the developing countries and getting this evidence into the hands of those who deliver healthcare is fundamental to improvements in healthcare delivery and health outcomes. 51 The findings from this study can provide useful up-to-date evidence on the landscape of SR and MA research and it is a wake-up call to balance generation of new knowledge and implementation by decision-makers.…”
Section: Discussionmentioning
confidence: 99%
“…How ever, the proper implementation of methodological standards in low-income countries, such as Ethiopia is poor. 21 Most health care decision-making tools were based on evidence from developed countries without considering the cultural and socioeconomic differences, and translation into context was limited. 22 Therefore, the increase in publication of high quality SR and MA can be helpful to improve the accuracy of context-specific decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…V literaturi raziskovalci povezujejo več individualnih ovir, ki učinkujejo na odnos in implementacijo na dokazih podprte prakse v klinična okolja (Dessie et al, 2020;Aynalem, Yazew, & Gebrie, 2021). Dagne, Beshah, Kassa, & Dagnaw (2021) ugotavljajo, da se izobraževanje iz raziskovanja in dokazih podprte prakse v zdravstveni negi pokažejo kot dejavniki, povezani tako s prepričanji kot implementacijo na dokazih podprte prakse.…”
Section: Uvodunclassified